Efektivitas Sistem Digital dalam Meningkatkan Penjualan di Toko Entus Collection Pasar Rau - Asep Munir Hidayat; Tubagus Hidayatulloh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Community service at Toko Entus Collection aimed to improve operational efficiency and sales through the implementation of a digital system. Students actively participated in managing social media, online promotions, and digital stock monitoring. Observations showed that digital media can disseminate product information widely, enhance consumer interaction, and support sales growth. Challenges included limited digital knowledge of the store manager, limited time for promotions, and inconsistent consumer responses. Direct guidance, socialization of digital media use, and adjustment of promotional strategies helped overcome these challenges. Students’ hands-on experience allowed the application of digital marketing theory to real business situations, while store managers benefited from improved operational performance. Therefore, this community service provides dual benefits: practical learning for students and increased competitiveness for SMEs.